NATIONAL STRATEGY FOR DEVELOPING COMPETITIVE ADVANTAGE THROUGH MILITARY-CIVIL FUSION - Sarjito, Aris (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2024)
Military-civil fusion (MCF) represents a strategic approach to enhancing national competitiveness by integrating defense and civilian sectors. This study to explore the theoretical foundations of MCF, its contribution to national competitiveness, and the alignment of national strategies with broader objectives. The research problems are understanding the theoretical underpinnings of MCF and their impact on national competitiveness, evaluating how national strategies facilitate the integration of defense and civilian sectors, and assessing the impact of MCF on technological innovation, industrial capability, and strategic resilience. The objectives of this study are to analyze the concept and theoretical basis of MCF, evaluate current national strategies and policies for MCF, and assess their alignment with security, innovation, and economic development goals. Additionally, the study examines the impact of MCF on key dimensions of national competitiveness. Using qualitative research methods and secondary data, the study discusses three main findings: the theoretical foundations of MCF and its contribution to national competitiveness, the alignment of national strategies for MCF with broader objectives, and the role of MCF in enhancing technological innovation and strategic resilience. The study concludes that effectively leveraging MCF can significantly contribute to a nation's competitive advantage by fostering technological advancements, industrial growth, and strategic resilience.